Rastlinski pripravki pri infekcijah urogenitalnega trakta - Kreft, Samo (Farmacevtski vestnik, 2011)
Urogenital infections can be treated with medicinal plants with direct antibacterial activity (Arctostaphylos uvae-ursi), plants that prevent the binding of bacteria to the mucosa (cranberry), and medicinal plants acting as diuretic (birch, nettle). Due to inconclusive clinical studies European Medicines Agency has not confirmed well-established use of any diuretic plants, only their traditional use was confirmed. This paper presents the state of research of individual plants.
Keywords: okužbe sečil; therapy; urogenitalne infekcije; zdravilne rastline; zdravljenje